Basalt fiber doped calcium-based heat storage material and preparation method thereof

By doping nano-SiO2 modified basalt fibers in CaO/Ca(OH)2 heat storage particles, the problems of easy particles breaking and uneven particle size are solved, and the mechanical strength and energy storage density of the heat storage particles are improved.

CN119859511APending Publication Date: 2025-04-22XIAN THERMAL POWER RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510063113.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

CaO/Ca(OH)2 heat storage particles are prone to shattering and uneven particle sizes in the fluidized bed and mobile bed thermal storage systems, resulting in blockage and large runner formation, hindering their promotion.

Method used

By mixing calcium hydroxide, nanosilicon dioxide and basalt fibers in a specific proportion, and undergoing shear, acid pretreatment and silane coupling agent modification, a calcium-based heat storage material doped with nano-SiO2 modified basalt fibers is formed.

Benefits of technology

It improves the mechanical strength and toughness of heat storage particles, reduces the possibility of particle breakage, enhances thermal conductivity, reduces the agglomeration between particles, and improves the effective energy storage density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859511A_ABST
    Figure CN119859511A_ABST
Patent Text Reader

Abstract

The invention discloses a basalt fiber doped calcium-based heat storage material and a preparation method thereof. The preparation method comprises the following steps: 1) weighing calcium hydroxide, nano silicon dioxide and basalt fibers; (2) carrying out shearing treatment on the basalt fiber to obtain the sheared basalt fiber; (3) pretreating the sheared basalt fibers obtained in the step (2) by using acid to obtain pretreated basalt fibers; 4) mixing absolute ethyl alcohol and distilled water, then adding a silane coupling agent KH550, then carrying out alcoholysis, then adding nano silicon dioxide, and then stirring to obtain a KH550 modified nano SiO2 (KH550 / SiO2) solution; (5) the basalt (KH550 / SiO2 / BF) fiber modified by the nanometer SiO2 is obtained; and (6) calcium hydroxide, the nano SiO2 modified basalt (KH550 / SiO2 / BF) fiber obtained in the step (5) and water are mixed and stirred, then extrusion rolling treatment is conducted, the heat storage particles are obtained, and the effective energy storage density of the heat storage particles prepared through the method is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermochemical heat storage, and relates to a basalt fiber-doped calcium-based heat storage material and a preparation method thereof. Background Art

[0002] Thermo-Chemical Energy Storage (TCES) is an efficient heat storage method that uses the reversible endothermic / exothermic reaction process of heat storage materials (i.e., the breaking and formation of chemical bonds during chemical changes) to store and release heat. The following is a detailed introduction to thermochemical heat storage technology: Principle: Thermochemical heat storage technology is based on reversible thermochemical reactions, and realizes the storage and release of thermal energy through the endothermic and exothermic characteristics of chemical reactions. In the endothermic reaction stage, energy is stored by breaking chemical bonds; in the exothermic reaction stage, energy is released by generating chemical bonds. Process: During the energy storage process, the reactants are decomposed into several products, and the resulting products are stored separately. When energy release is required, the products are brought into contact to produce an exothermic reaction to achieve the release of thermal energy.

[0003] The patent with publication number CN114836028A discloses a nano-silicon dioxide and silane coupling agent modified basalt fiber synergistically reinforced polyamide and a preparation method thereof. The nano-silicon dioxide and silane coupling agent modified basalt fiber synergistically reinforced polyamide comprises polyamide resin as a matrix material component A, basalt fiber as a reinforcing material component B, nano-silicon dioxide as a fiber-modified component C, and a silane coupling agent that can modify the fiber surface and serve as an adhesive component D, and the amounts thereof are respectively: the component A is 40-90%, the component B is 10-60%, the component C is 0.1-0.5%, the component D is 0.1-1%, the component C is 0.2-0.3%, and the component D is 0.2-0.5%. The preparation method of nano-silicon dioxide and silane coupling agent modified basalt fiber synergistically reinforced polyamide comprises the following steps: S1, adding basalt fiber to silane coupling agent solution, placing in a 30-60°C oven for heating reaction for 2-6 hours, then taking out, filtering and placing in a 100-140°C oven for reaction for 1-4 hours, and taking out for standby after the treatment is completed; S2, ultrasonically dispersing nano-silicon dioxide in ethanol solution, slowly dropping silane coupling agent into the dispersion, stirring and reacting at a reflux temperature of 70-90°C for 4-6 hours, and then washing by centrifugation to obtain nano-silicon dioxide grafted with silane coupling agent, and drying and storing for standby; S3, Silane coupling agent modified nano-silica is ultrasonically dispersed in an ethanol solution, and silane coupling agent modified basalt fiber is added, and the mixture is reacted in a constant temperature water bath at 70-90° C. for 0.5-2 h, and then taken out and reacted in an oven at 110-130° C. for 1-3 h to obtain basalt fiber with surface grafted nano-silica; S4, the basalt fiber with surface grafted nano-silica and polyamide are added into a twin-screw extruder in two parts for blending, and then the blend is placed in the extruder, and injection molded out of a mold at a temperature of 230-240° C. and a pressure of 750-850 MPa to obtain a modified basalt fiber synergistically reinforced polyamide composite material.

[0004] Thermochemical heat storage technology is a new type of heat storage technology with the advantages of high heat storage density and cross-seasonal heat storage. 2 Due to its cheapness and availability, it has broad application prospects. 2 The particles are easy to break and have uneven particle size. After being broken and agglomerated, they are prone to blockage and form large flow channels, which hinders their promotion in fluidized bed and moving bed thermochemical heat storage systems.

[0005] The current solution is to enhance the mechanical strength of the particles by adding alumina, silicon carbide, diatomaceous earth, etc., or to improve the particle's resistance to crushing by wrapping it with a hard shell. However, the amount added is often greater than 20%, which greatly reduces the effective energy storage density of the heat storage particles. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a basalt fiber-doped calcium-based heat storage material and a preparation method thereof. The heat storage particles prepared by the method have a high effective energy storage density.

[0007] To achieve the above object, the present invention discloses a method for preparing a basalt fiber-doped calcium-based heat storage material, comprising the following steps:

[0008] 1) Weigh calcium hydroxide, nano-silicon dioxide and basalt fiber;

[0009] 2) shearing the basalt fiber to obtain sheared basalt fiber;

[0010] 3) pretreating the sheared basalt fiber obtained in step 2) with an acid to obtain pretreated basalt fiber;

[0011] 4) Anhydrous ethanol and distilled water are mixed, and then the silane coupling agent KH550 is added, followed by alcoholysis, followed by the addition of nano-silica, and then stirred to obtain KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution;

[0012] 5) Place the pretreated basalt fiber into the KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution, stirring again, then taking out the fiber in the solution, and drying it to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fiber;

[0013] 6) Calcium hydroxide, the nano-SiO2-modified basalt (KH550 / SiO2 / BF) fiber obtained in step 5) and water are mixed and stirred, and then extruded and spheronized to obtain heat storage particles.

[0014] The further improvement of the preparation method of the basalt fiber-doped calcium-based heat storage material of the present invention is:

[0015] Furthermore, in step 1), the mass ratio of calcium hydroxide, nano-silicon dioxide and basalt fiber is 1:0.1:0.02.

[0016] Furthermore, in step 2), the particle size of the basalt fiber after shearing is 0.5-1 mm.

[0017] Further, the process of step 3) is:

[0018] The sheared basalt fiber obtained in step 2) is immersed in a 1M sulfuric acid solution, heated to 60°C and kept warm for 2 hours, then washed with deionized water, and then dried at 180°C for 2 hours to obtain pretreated basalt fiber.

[0019] Further, the process of step 4) is:

[0020] Anhydrous ethanol and distilled water were mixed, and then the silane coupling agent KH550 was added, and then alcoholyzed at 65°C in a constant temperature water bath for 30 minutes, and then nano-silica was added, and then stirred at 50°C for 1 hour to obtain KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution.

[0021] Furthermore, the ratio of anhydrous ethanol, distilled water, silane coupling agent KH550 and nano-silicon dioxide is 135 mL: 15 mL: 3 mL: 10 g.

[0022] Further, the process of step 5) is:

[0023] The pretreated basalt fiber was placed in KH550 modified nano-SiO 2 The solution was stirred at 50 °C for 1 h, and then the fibers in the solution were taken out and placed in a blast oven at 120 °C for 2 h to obtain nano-SiO 2 Modified basalt (KH550 / SiO2 / BF) fiber.

[0024] Furthermore, in step 6), the mass of water is 30% of the mass of calcium hydroxide.

[0025] Furthermore, in step 6), the particle size of the heat storage particles is 2 mm to 3 mm.

[0026] The invention discloses a basalt fiber-doped calcium-based heat storage material, which is prepared based on a preparation method of the basalt fiber-doped calcium-based heat storage material.

[0027] The present invention has the following beneficial effects:

[0028] The basalt fiber-doped calcium-based heat storage material and preparation method thereof described in the present invention are specifically operated by using an acid to pretreat the sheared basalt fiber to obtain the pretreated basalt fiber, wherein a large number of hydroxyl groups are exposed on the surface of the acid-treated basalt fiber, and these hydroxyl groups form hydrogen bonds with the hydroxyl groups of calcium hydroxide, thereby increasing the adhesion between the basalt fiber and the calcium hydroxide, greatly reducing the polarity between the calcium hydroxide particles, thereby reducing the possibility of agglomeration between the calcium hydroxide particles. In addition, by doping with basalt fibers, the mechanical strength and toughness of the calcium hydroxide heat storage particles can be greatly improved, thereby reducing the possibility of particle breakage. In addition, by adding silicon dioxide, on the one hand, the thermal conductivity of the calcium hydroxide heat storage material can be improved, and on the other hand, the distance between the calcium hydroxide particles is increased, reducing the possibility of agglomeration, and then increasing the effective energy storage density of the heat storage particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0030] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the description of the present invention, it should be understood that the terms “include” and “comprises” indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.

[0033] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0034] It should be further understood that the term "and / or" used in the present specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects are in an "or" relationship.

[0035] It should be understood that, although the terms first, second, third, etc. may be used to describe preset ranges, etc. in the embodiments of the present invention, these preset ranges should not be limited to these terms. These terms are only used to distinguish preset ranges from each other. For example, without departing from the scope of the embodiments of the present invention, the first preset range may also be referred to as the second preset range, and similarly, the second preset range may also be referred to as the first preset range.

[0036] The word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining" or "in response to detecting", depending on the context. Similarly, the phrases "if it is determined" or "if (stated condition or event) is detected" may be interpreted as "when it is determined" or "in response to determining" or "when detecting (stated condition or event)" or "in response to detecting (stated condition or event)", depending on the context.

[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.

[0039] refer to Figure 1The method for preparing the basalt fiber-doped calcium-based heat storage material of the present invention comprises the following steps:

[0040] 1) weighing calcium hydroxide, nano-silicon dioxide and basalt fiber, wherein the mass ratio of calcium hydroxide, nano-silicon dioxide and basalt fiber is 1:0.1:0.02, wherein the mass of calcium hydroxide is 100 g;

[0041] 2) subjecting the basalt fiber to high-speed shearing for 30 minutes to obtain a material with a particle size of 0.5 to 1 mm;

[0042] 3) immersing the basalt fiber obtained in step 2) in a 1M sulfuric acid solution, heating to 60°C and keeping the temperature for 2 hours, washing with deionized water, and then drying in an oven at 180°C for 2 hours, taking out for use, and obtaining pretreated basalt fiber;

[0043] 4) 135 mL of anhydrous ethanol and 15 mL of distilled water were mixed, and then 3 mL of silane coupling agent KH550 was added, and then alcoholyzed at 65 ° C for 30 min in a constant temperature water bath, and then nano-silica was added, and then stirred at 50 ° C for 1 h to obtain KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution.

[0044] 5) Place the pretreated basalt fiber into KH550 modified nano-SiO 2 The solution was stirred at 50°C for 1 h, and then the fibers in the solution were taken out and placed in a blast oven at 120°C for 2 h to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fibers.

[0045] 6) Calcium hydroxide, the nano-SiO2-modified basalt (KH550 / SiO2 / BF) fiber obtained in step 5) and water are mixed and stirred for 30 minutes, wherein the mass of water is 30% of the mass of calcium hydroxide, and then extruded and spheronized to obtain heat storage particles with a particle size of 2 to 3 mm.

[0046] The present invention discloses a basalt fiber-doped calcium-based heat storage material, which is prepared based on a preparation method of the basalt fiber-doped calcium-based heat storage material. The preparation method of the basalt fiber-doped calcium-based heat storage material comprises the following steps:

[0047] 1) Weigh calcium hydroxide, nano-silicon dioxide and basalt fiber;

[0048] 2) shearing the basalt fiber to obtain sheared basalt fiber;

[0049] 3) pretreating the sheared basalt fiber obtained in step 2) with an acid to obtain pretreated basalt fiber;

[0050] 4) Anhydrous ethanol and distilled water are mixed, and then the silane coupling agent KH550 is added, followed by alcoholysis, followed by the addition of nano-silica, and then stirred to obtain KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution;

[0051] 5) Place the pretreated basalt fiber into the KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution, stirring again, then taking out the fiber in the solution, and drying it to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fiber;

[0052] 6) Calcium hydroxide, the nano-SiO2-modified basalt (KH550 / SiO2 / BF) fiber obtained in step 5) and water are mixed and stirred, and then extruded and spheronized to obtain heat storage particles.

[0053] Embodiment 1

[0054] The method for preparing the basalt fiber-doped calcium-based heat storage material of the present invention comprises the following steps:

[0055] 1) weighing calcium hydroxide, nano-silicon dioxide and basalt fiber, wherein the mass ratio of calcium hydroxide, nano-silicon dioxide and basalt fiber is 1:0.1:0.02, wherein the mass of calcium hydroxide is 100 g;

[0056] 2) subjecting the basalt fiber to high-speed shearing for 30 minutes to obtain a material with a particle size of 0.8 mm;

[0057] 3) immersing the basalt fiber obtained in step 2) in a 1M sulfuric acid solution, heating to 60°C and keeping the temperature for 2 hours, washing with deionized water, and then drying in an oven at 180°C for 2 hours, taking out for use, and obtaining pretreated basalt fiber;

[0058] 4) 135 mL of anhydrous ethanol and 15 mL of distilled water were mixed, and then 3 mL of silane coupling agent KH550 was added, and then alcoholyzed at 65 ° C for 30 min in a constant temperature water bath, and then nano-silica was added, and then stirred at 50 ° C for 1 h to obtain KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution.

[0059] 5) Place the pretreated basalt fiber into KH550 modified nano-SiO2 The solution was stirred at 50°C for 1 h, and then the fibers in the solution were taken out and placed in a blast oven at 120°C for 2 h to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fibers.

[0060] 6) Calcium hydroxide, the nano-SiO2-modified basalt (KH550 / SiO2 / BF) fiber obtained in step 5) and water are mixed and stirred for 30 minutes, wherein the mass of water is 30% of the mass of calcium hydroxide, and then extruded and spheronized to obtain heat storage particles with a particle size of 2.5 mm.

[0061] Embodiment 2

[0062] The method for preparing the basalt fiber-doped calcium-based heat storage material of the present invention comprises the following steps:

[0063] 1) weighing calcium hydroxide, nano-silicon dioxide and basalt fiber, wherein the mass ratio of calcium hydroxide, nano-silicon dioxide and basalt fiber is 1:0.1:0.02, wherein the mass of calcium hydroxide is 100 g;

[0064] 2) subjecting the basalt fiber to high-speed shearing for 30 minutes to obtain a material with a particle size of 1 mm;

[0065] 3) immersing the basalt fiber obtained in step 2) in a 1M sulfuric acid solution, heating to 60°C and keeping the temperature for 2 hours, washing with deionized water, and then drying in an oven at 180°C for 2 hours, taking out for use, and obtaining pretreated basalt fiber;

[0066] 4) 135 mL of anhydrous ethanol and 15 mL of distilled water were mixed, and then 3 mL of silane coupling agent KH550 was added, and then alcoholyzed at 65 ° C for 30 min in a constant temperature water bath, and then nano-silica was added, and then stirred at 50 ° C for 1 h to obtain KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution.

[0067] 5) Place the pretreated basalt fiber into KH550 modified nano-SiO 2 The solution was stirred at 50°C for 1 h, and then the fibers in the solution were taken out and placed in a blast oven at 120°C for 2 h to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fibers.

[0068] 6) Calcium hydroxide, the nano-SiO2-modified basalt (KH550 / SiO2 / BF) fiber obtained in step 5) and water are mixed and stirred for 30 minutes, wherein the mass of water is 30% of the mass of calcium hydroxide, and then extruded and spheronized to obtain heat storage particles with a particle size of 3 mm.

[0069] Embodiment 3

[0070] The method for preparing the basalt fiber-doped calcium-based heat storage material of the present invention comprises the following steps:

[0071] 1) weighing calcium hydroxide, nano-silicon dioxide and basalt fiber, wherein the mass ratio of calcium hydroxide, nano-silicon dioxide and basalt fiber is 1:0.1:0.02, wherein the mass of calcium hydroxide is 100 g;

[0072] 2) subjecting the basalt fiber to high-speed shearing for 30 minutes to obtain a material with a particle size of 0.5 mm;

[0073] 3) immersing the basalt fiber obtained in step 2) in a 1M sulfuric acid solution, heating to 60°C and keeping the temperature for 2 hours, washing with deionized water, and then drying in an oven at 180°C for 2 hours, taking out for use, and obtaining pretreated basalt fiber;

[0074] 4) 135 mL of anhydrous ethanol and 15 mL of distilled water were mixed, and then 3 mL of silane coupling agent KH550 was added, and then alcoholyzed at 65 ° C for 30 min in a constant temperature water bath, and then nano-silica was added, and then stirred at 50 ° C for 1 h to obtain KH550 modified nano-SiO 2 (KH550 / SiO 2 ) solution.

[0075] 5) Place the pretreated basalt fiber into KH550 modified nano-SiO 2 The solution was stirred at 50°C for 1 h, and then the fibers in the solution were taken out and placed in a blast oven at 120°C for 2 h to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fibers.

[0076] 6) Calcium hydroxide, the nano-SiO2-modified basalt (KH550 / SiO2 / BF) fiber obtained in step 5) and water are mixed and stirred for 30 minutes, wherein the mass of water is 30% of the mass of calcium hydroxide, and then extruded and spheronized to obtain heat storage particles with a particle size of 2 mm.

[0077] The heat storage experiment process is as follows: take 10g of the heat storage medium prepared above, put it into a tube furnace for heating for a certain period of time, then cool it to room temperature and weigh it, and calculate the decomposition efficiency of the heat storage medium. The results show that after 30 minutes, the decomposition efficiency of the heat storage medium generated at 500℃, 550℃, and 600℃ reached 78%, 83%, and 95%, respectively, which is higher than that of pure Ca(OH) 2 After ten cycles, the molar fractions of the remaining effective heat storage material calcium hydroxide in the heat storage medium generated at 500°C, 550°C, and 600°C were 82%, 85%, and 89%, respectively, which were higher than pure Ca(OH) 2 The mole fraction of CaO, an effective heat storage material, is 40%, 45% and 52%.

[0078] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and disclosure of the invention. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.

[0079] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

[0080] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a basalt fiber-doped calcium-based heat storage material, characterized in that: The following steps are involved: 1) Weigh calcium hydroxide, nano-silicon dioxide and basalt fiber; 2) shearing the basalt fiber to obtain sheared basalt fiber; 3) pretreating the sheared basalt fiber obtained in step 2) with an acid to obtain pretreated basalt fiber; 4) Anhydrous ethanol and distilled water are mixed, and then a silane coupling agent KH550 is added, followed by alcoholysis, followed by addition of nano-silicon dioxide, and stirring to obtain a KH550-modified nano-SiO2 (KH550 / SiO2) solution; 5) placing the pretreated basalt fiber into the KH550 modified nano-SiO2 (KH550 / SiO2) solution obtained in step 4), stirring the solution, taking out the fiber from the solution, and drying the solution to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fiber; 6) Calcium hydroxide, the nano-SiO2-modified basalt (KH550 / SiO2 / BF) fiber obtained in step 5) and water are mixed and stirred, and then extruded and spheronized to obtain heat storage particles.

2. The method for preparing the basalt fiber-doped calcium-based heat storage material according to claim 1, characterized in that: In step 1), the mass ratio of calcium hydroxide, nano-silicon dioxide and basalt fiber is 1:0.1:0.

02.

3. The method for preparing the basalt fiber-doped calcium-based heat storage material according to claim 1, characterized in that: In step 2), the particle size of the basalt fiber after shearing is 0.5-1 mm.

4. The method for preparing basalt fiber-doped calcium-based heat storage material according to claim 1, characterized in that: The process of step 3) is: The sheared basalt fiber obtained in step 2) is immersed in a 1M sulfuric acid solution, heated to 60°C and kept warm for 2 hours, then washed with deionized water, and then dried at 180°C for 2 hours to obtain pretreated basalt fiber.

5. The method for preparing basalt fiber-doped calcium-based heat storage material according to claim 1, characterized in that: The process of step 4) is: Anhydrous ethanol and distilled water were mixed, and then the silane coupling agent KH550 was added, followed by alcoholysis at 65°C for 30 minutes in a constant temperature water bath, followed by adding nano-silica, and then stirring at 50°C for 1 hour to obtain a KH550 modified nano-SiO2 (KH550 / SiO2) solution.

6. The method for preparing the basalt fiber-doped calcium-based heat storage material according to claim 5, characterized in that: The ratio of anhydrous ethanol, distilled water, silane coupling agent KH550 and nano-silicon dioxide is 135mL:15mL:3mL:10g.

7. The method for preparing basalt fiber-doped calcium-based heat storage material according to claim 1, characterized in that: The process of step 5) is: The pretreated basalt fiber was placed in a KH550 modified nano-SiO2 solution, stirred at 50°C for 1 h, then the fiber in the solution was taken out and placed in a blast oven at 120°C for 2 h to obtain nano-SiO2 modified basalt (KH550 / SiO2 / BF) fiber.

8. The method for preparing basalt fiber-doped calcium-based heat storage material according to claim 1, characterized in that: In step 6), the mass of water is 30% of the mass of calcium hydroxide.

9. The method for preparing basalt fiber-doped calcium-based heat storage material according to claim 1, characterized in that: In step 6), the particle size of the heat storage particles is 2 mm to 3 mm.

10. A basalt fiber-doped calcium-based heat storage material, characterized in that: The material is prepared based on the preparation method of the basalt fiber-doped calcium-based heat storage material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nano silicon dioxide and silane coupling agent modified basalt fiber synergistically reinforced polyamide and preparation method thereof

    CN114836028A

  • Calcium-based thermochemical heat storage material and preparation method thereof

    CN117946635A

  • High-entropy fluorite oxide modified calcium-based thermochemical heat storage material and preparation method thereof

    CN118272056A

  • Preparation method of composite calcium-based thermochemical heat storage particles

    CN118771826A